Moisture absorption expansion composite material and preparation method and application thereof
By preparing a moisture-absorbing and expansion composite material containing chemical fertilizers, sodium alginate, calcium chloride solution and sodium polyacrylate powder, the problem of low soil slab and fertilizer utilization in saline-alkali land is solved, and the soil moisture condition and permeability are improved and the effective release of fertilizer.
Patent Information
- Application Number
- CN202510000183.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-02
- Publication Date
- 2025-02-07
- Estimated Expiration
- 2045-01-02
AI Technical Summary
The soil in saline-alkali land has poor slab bonding and poor permeability due to high salt content and high pH, which affects crop growth. Traditional fertilizer application has aggravated the slab bonding problem, and hydrogel materials are hydrolyzed quickly in this environment and have low effective substance content.
A hygroscopic expansion composite material, including fertilizer, sodium alginate, calcium chloride solution and sodium polyacrylate powder, is prepared by granulation, drying, forming a viscous adsorption gel and a coating, forming a stable and tougher Strong gel envelope improves the water absorption, expansion and physical properties of composite materials.
Significantly improve the moisture condition and permeability of saline-alkali soil, improve fertilizer utilization, extend the release time of effective substances, alleviate soil slab problems, and help soil desalination.
Smart Images

Figure CN119390502A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of soil improvement, and in particular to a hygroscopic expansion composite material and a preparation method and application thereof. Background Art
[0002] Polymer hydrogel materials have excellent water absorption and water retention, and are widely used in the fields of health and medicine. With the continuous development of modern agricultural technology, hydrogel materials have shown good prospects in soil improvement. Mixing improved materials with hydrogels can modify hydrogel materials and can be used as a new agricultural technology for soil improvement. However, the spherical hydrogel materials contain less effective substances, and the hydrogel spheres themselves are fragile and have a short action time. Especially in saline-alkali land with high salt content and high pH, they will hydrolyze quickly.
[0003] The high salt content in saline-alkali land can easily lead to soil compaction, poor permeability, and difficulty in effectively penetrating and retaining water, which in turn affects the normal growth of crops. The application of traditional chemical fertilizers will aggravate the compaction of saline-alkali land, causing the soil structure to deteriorate, leading to setbacks in saline-alkali land improvement.
[0004] How to apply hydrogel materials to the comprehensive improvement of saline-alkali soil is of great strategic significance for ensuring national food security. Summary of the invention
[0005] In view of the deficiencies in the above-mentioned prior art, the present invention provides a hygroscopic and expandable composite material capable of improving the moisture condition and permeability of soil and increasing fertilizer utilization, as well as a preparation method and application thereof.
[0006] The present invention provides a hygroscopic and expandable composite material, comprising the following raw material components in parts by weight: 65-70 parts of fertilizer, 7-10 parts of sodium alginate, 20-25 parts of calcium chloride solution, and 1-2 parts of sodium polyacrylate powder.
[0007] In some embodiments of the present application, the mass percentage concentration of the calcium chloride solution is 0.1%-0.5%.
[0008] As another aspect of the present application, a method for preparing the above-mentioned hygroscopic and expandable composite material is also provided, which specifically comprises the following steps: S1. Granulation: The fertilizer and sodium alginate are mixed and ground in proportion to obtain a composite material, the composite material is put into a granulator, and a calcium chloride solution is sprayed to control the humidity of the composite material within a certain range, and the granulator is started to granulate to obtain composite particles; S2. Drying: Drying the composite particles at 55-60°C for 12-24 hours; S3, forming a viscous adsorption gel: Spraying the calcium chloride solution onto the dried composite particles while stirring, so that the calcium chloride solution is evenly coated on the surface of the composite particles to form a viscous adsorption gel; S4, Encapsulation: Adding sodium polyacrylate powder to the composite particles that form the viscous adsorption gel in step S3, and stirring the mixture, so that the sodium polyacrylate powder is uniformly adsorbed on the surface of the composite particles to form a coating gel, thereby obtaining coated composite particles; S5, Secondary drying and shaping: Drying the coated composite particles at 55-60° C. for 12-24 hours to dry the coating gel to form a solid coating; S6. Repeat steps S3-S5 until the thickness of the coating on the surface of the coated composite particles reaches the required value, thereby obtaining the composite material.
[0009] In some embodiments of the present application, in step S1, when the fineness of the composite material is 60-80 mesh, grinding is stopped and the composite material is placed in a granulator.
[0010] In some embodiments of the present application, in step S1, the humidity of the composite material is controlled at 15-20%, and too low or too high a humidity will affect the granulation effect.
[0011] In some embodiments of the present application, in step S3, the viscous adsorption gel is formed by the reaction of the calcium chloride solution and the sodium alginate on the surface of the composite particles, and the reaction formula is as follows: 2C 17 H 35 COO - +Ca 2+ ==(C 17 H 35 COO)2Ca In some embodiments of the present application, in step S3, the spraying amount of the calcium chloride solution does not exceed 5%-7% of the weight of the composite particles.
[0012] In some embodiments of the present application, in step S4, the fineness of the sodium polyacrylate powder is between 80-100 mesh.
[0013] In some embodiments of the present application, in step S4, the adding speed of the sodium polyacrylate is 5%-10% / min of the total adding mass of the sodium polyacrylate powder, and the stirring speed is 10-15 r / min.
[0014] As another aspect of the present application, the water-swellable composite material prepared by the above-mentioned preparation method is applied to the improvement of saline-alkali land, and the surface coating is formed from a semi-solid gel state by water absorption and expansion in the solid state, and the nutrients in the fertilizer are slowly released into the soil through the gel, and a microenvironment with a higher water content is formed in the soil. After the soil loses water, the coating also loses water and returns to a solid state, and no longer releases the nutrients in the fertilizer; after the soil is rehydrated again, the coating absorbs water and expands into a gel state again, and slowly releases the nutrients again, and the above process is repeated many times until all the nutrients in the fertilizer are released, and the coating gradually decomposes during the process of water absorption and water loss.
[0015] Based on the above technical scheme, the present invention adopts sodium alginate, a hygroscopic and swellable polymer material, to improve the compaction problem. After sodium alginate is applied to the soil, it swells when it meets water, and can maintain the bulk density and structure of the soil. This solves the problem that traditional chemical fertilizers have almost no expansion when they meet water after application, and dissolve in a short time. The ions in the fertilizer react with the soil particles, and the aggregates are destroyed when the soil loses water, causing compaction. Chemical fertilizers are used in saline-alkali land, overcoming the technical prejudice that traditional chemical fertilizers cannot be used in saline-alkali land and aggravate compaction. In order to solve the problem that the sodium alginate gel in the composite material is not strong enough and is easily broken and hydrolyzed in a high-salt and high-pH environment, calcium chloride solution is sprayed and a gel coating with stronger stability and toughness is formed by cross-linking the calcium chloride solution and sodium polyacrylate to improve the physical properties of the composite material such as water absorption, expansion and toughness, and improve the strength of the composite material. Composite materials with a specific coating thickness can be formulated through multiple coatings, which can effectively cope with the harsh environment of saline-alkali land. The composite material is stable after absorbing water and swelling, and its volume expands more than 5 times. When 10% of the composite material is added to the surface compacted soil, when the soil has sufficient moisture, the soil water holding capacity can be increased by 2-5%, and the soil bulk density can be reduced by 20-30%, which can significantly improve the problem of saline-alkali soil compaction. At the same time, as the coating slowly decomposes, the nutrients and calcium ions in the fertilizer are slowly released and exchanged with the sodium ions in the soil, which is beneficial to the desalination of saline-alkali soil. BRIEF DESCRIPTION OF THE DRAWINGS
[0016] The drawings described herein are used to provide a further understanding of the present invention and constitute a part of this application. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute an improper limitation of the present invention. In the drawings: Figure 1 is the swelling ratio of the composite material prepared in Examples 1-5 of the present invention; Figure 2 It is a comparison diagram of water absorption and expansion of the composite material particles of Comparative Example 1, Comparative Example 2, and Example 6; Figure 3 Schematic diagram of the diameter change of the composite material particles of Comparative Example 1, Comparative Example 2 and Example 6 after absorbing water. DETAILED DESCRIPTION
[0017] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0018] Example 1 S1. Granulation: 65 parts of commercially available common fertilizer and 7 parts of sodium alginate are mixed and ground until the particle fineness is 60-80 meshes to obtain a composite material, the composite material is put into a disc granulator, and 20 parts of a calcium chloride solution with a mass percentage concentration of 0.5% is sprayed, the humidity of the composite material is measured by a soil moisture sensor, and the humidity of the composite material powder is controlled at about 15-20%, too low or too high will affect the granulation effect, the disc granulator is started for granulation, and when the granulation diameter reaches 3-4 mm, the disc granulator is stopped to obtain composite particles; S2. Drying: Start the hot air drying function of the disc granulator, set the drying temperature at 55 °C, and dry for 12 h; S3, forming a viscous adsorption gel: 5 parts of calcium chloride solution with a mass percentage concentration of 0.5% are loaded into the spraying device and sprayed on the dried composite particles. At the same time, the stirring function of the disc granulator is started to stir, so that the calcium chloride solution is evenly coated on the surface of the composite particles and reacts with the sodium alginate on the surface as follows: 2C 17 H 35 COO - +Ca 2+ ==(C 17 H 35 COO)2Ca A viscous adsorption gel is formed, and the amount of calcium chloride solution sprayed in this step does not exceed 6% of the mass of the composite particles; S4, Encapsulation: Start the stirring function of the disc granulator, add 1 part of sodium polyacrylate powder with a fineness of 80-100 mesh to the material feeding device, the added amount is about 1.1% of the total mass of the composite particles obtained in step S3, slowly feed the sodium polyacrylate powder into the disc granulator at a feeding speed of (5%×1 part) / min, and stir at a speed of 10 r / min, so that the sodium polyacrylate powder is uniformly adsorbed on the surface of the composite particles to form a coating gel, and obtain coated composite particles; S5, Secondary drying and shaping: The hot air drying function of the disc granulator is started to dry the coated composite granules at 55° C. for 12 hours to dry the coating gel to form a solid coating; S6. Repeat steps S3-S5 2-3 times until the thickness of the coating on the surface of the coated composite particles reaches 1-2 mm, thereby obtaining the composite material.
[0019] Example 2 S1. Granulation: 65 parts of commercially available common fertilizer and 7 parts of sodium alginate are mixed and ground until the particle fineness is 60-80 meshes to obtain a composite material, the composite material is put into a disc granulator, and 20 parts of a calcium chloride solution with a mass percentage concentration of 0.1% is sprayed, the humidity of the composite material is measured by a soil moisture sensor, and the humidity of the composite material powder is controlled at about 15-20%, too low or too high will affect the granulation effect, the disc granulator is started for granulation, and when the granulation diameter reaches 3-4 mm, the disc granulator is stopped to obtain composite particles; S2. Drying: Start the hot air drying function of the disc granulator, set the drying temperature at 55 °C, and dry for 12 h; S3, forming a viscous adsorption gel: 5 parts of calcium chloride solution with a mass percentage concentration of 0.1% are loaded into the spraying device and sprayed onto the dried composite particles. At the same time, the stirring function of the disc granulator is started to stir, so that the calcium chloride solution is evenly coated on the surface of the composite particles and reacts with the sodium alginate on the surface as follows: 2C 17 H 35 COO - +Ca 2+ ==(C 17 H 35 COO)2Ca A viscous adsorption gel is formed, and the amount of calcium chloride solution sprayed in this step does not exceed 5% of the mass of the composite particles; S4, Encapsulation: Start the stirring function of the disc granulator, add 1 part of sodium polyacrylate powder with a fineness of 80-100 mesh to the material feeding device, the added amount is about 1.1% of the total mass of the composite particles obtained in step S3, slowly feed the sodium polyacrylate powder into the disc granulator at a feeding speed of (5%×1 part) / min, and stir at a speed of 10 r / min, so that the sodium polyacrylate powder is uniformly adsorbed on the surface of the composite particles to form a coating gel, and obtain coated composite particles; S5, Secondary drying and shaping: The hot air drying function of the disc granulator is started to dry the coated composite granules at 55° C. for 12 hours to dry the coating gel to form a solid coating; S6. Repeat steps S3-S5 2-3 times until the thickness of the coating on the surface of the coated composite particles reaches 1-2 mm, thereby obtaining the composite material.
[0020] Example 3 S1. Granulation: 65 parts of commercially available common fertilizer and 7 parts of sodium alginate are mixed and ground until the particle fineness is 60-80 meshes to obtain a composite material, the composite material is put into a disc granulator, and 20 parts of a calcium chloride solution with a mass percentage concentration of 0.3% is sprayed, the humidity of the composite material is measured by a soil moisture sensor, and the humidity of the composite material powder is controlled at about 15-20%, too low or too high will affect the granulation effect, the disc granulator is started for granulation, and when the granulation diameter reaches 3-4 mm, the disc granulator is stopped to obtain composite particles; S2. Drying: Start the hot air drying function of the disc granulator, set the drying temperature at 55°C, and dry for 12 h; S3, forming a viscous adsorption gel: 5 parts of calcium chloride solution with a mass percentage concentration of 0.3% are loaded into the spraying device and sprayed on the dried composite particles. At the same time, the stirring function of the disc granulator is started to stir, so that the calcium chloride solution is evenly coated on the surface of the composite particles and reacts with the sodium alginate on the surface as follows: 2C 17 H 35 COO - +Ca 2+ ==(C 17 H 35 COO)2Ca A viscous adsorption gel is formed, and the amount of calcium chloride solution sprayed in this step does not exceed 6% of the mass of the composite particles; S4, Encapsulation: Start the stirring function of the disc granulator, add 1 part of sodium polyacrylate powder with a fineness of 80-100 mesh to the material feeding device, the added amount is about 1.1% of the total mass of the composite particles obtained in step S3, slowly feed the sodium polyacrylate powder into the disc granulator at a feeding speed of (5%×1 part) / min, and stir at a speed of 10 r / min, so that the sodium polyacrylate powder is uniformly adsorbed on the surface of the composite particles to form a coating gel, and obtain coated composite particles; S5, Secondary drying and shaping: The hot air drying function of the disc granulator is started to dry the coated composite granules at 55°C for 12 hours to dry the coating gel to form a solid coating; S6. Repeat steps S3-S5 2-3 times until the thickness of the coating on the surface of the coated composite particles reaches 1-2 mm, thereby obtaining the composite material.
[0021] Example 4 S1. Granulation: 65 parts of commercially available common fertilizer and 7 parts of sodium alginate are mixed and ground until the particle fineness is 60-80 meshes to obtain a composite material, the composite material is put into a disc granulator, and 20 parts of a calcium chloride solution with a mass percentage concentration of 1% is sprayed, the humidity of the composite material is measured by a soil moisture sensor, and the humidity of the composite material powder is controlled at about 15-20%, too low or too high will affect the granulation effect, the disc granulator is started for granulation, and when the granulation diameter reaches 3-4 mm, the disc granulator is stopped to obtain composite particles; S2. Drying: Start the hot air drying function of the disc granulator, set the drying temperature at 55 °C, and dry for 12 h; S3, forming a viscous adsorption gel: 5 parts of calcium chloride solution with a mass percentage concentration of 1% are loaded into the spraying device and sprayed on the dried composite particles. At the same time, the stirring function of the disc granulator is started to stir, so that the calcium chloride solution is evenly coated on the surface of the composite particles and reacts with the sodium alginate on the surface as follows: 2C 17 H 35 COO - +Ca 2+ ==(C 17 H 35 COO)2Ca A viscous adsorption gel is formed, and the amount of calcium chloride solution sprayed in this step does not exceed 6% of the mass of the composite particles; S4, Encapsulation: Start the stirring function of the disc granulator, add 1 part of sodium polyacrylate powder with a fineness of 80-100 mesh to the material feeding device, the added amount is about 1.1% of the total mass of the composite particles obtained in step S3, slowly feed the sodium polyacrylate powder into the disc granulator at a feeding speed of (5%×1 part) / min, and stir at a speed of 10 r / min, so that the sodium polyacrylate powder is uniformly adsorbed on the surface of the composite particles to form a coating gel, and obtain coated composite particles; S5, Secondary drying and shaping: The hot air drying function of the disc granulator is started to dry the coated composite granules at 55°C for 12 hours to dry the coating gel to form a solid coating; S6. Repeat steps S3-S5 2-3 times until the thickness of the coating on the surface of the coated composite particles reaches 1-2 mm, thereby obtaining the composite material.
[0022] Example 5 S1. Granulation: 65 parts of commercially available common fertilizer and 7 parts of sodium alginate are mixed and ground until the particle fineness is 60-80 meshes to obtain a composite material, the composite material is put into a disc granulator, and 20 parts of a calcium chloride solution with a mass percentage concentration of 3% is sprayed, the humidity of the composite material is measured by a soil moisture sensor, and the humidity of the composite material powder is controlled at about 15-20%, too low or too high will affect the granulation effect, the disc granulator is started for granulation, and when the granulation diameter reaches 3-4 mm, the disc granulator is stopped to obtain composite particles; S2. Drying: Start the hot air drying function of the disc granulator, set the drying temperature at 55 °C, and dry for 12 h; S3, forming a viscous adsorption gel: 5 parts of calcium chloride solution with a mass percentage concentration of 3% are loaded into the spraying device and sprayed on the dried composite particles. At the same time, the stirring function of the disc granulator is started to stir, so that the calcium chloride solution is evenly coated on the surface of the composite particles and reacts with the sodium alginate on the surface as follows: 2C 17 H 35 COO - +Ca 2+ ==(C 17 H 35 COO)2Ca A viscous adsorption gel is formed, and the amount of calcium chloride solution sprayed in this step does not exceed 6% of the mass of the composite particles; S4, Encapsulation: Start the stirring function of the disc granulator, add 1 part of sodium polyacrylate powder with a fineness of 80-100 mesh to the material feeding device, the added amount is about 1.1% of the total mass of the composite particles obtained in step S3, slowly feed the sodium polyacrylate powder into the disc granulator at a feeding speed of (5%×1 part) / min, and stir at a speed of 10 r / min, so that the sodium polyacrylate powder is uniformly adsorbed on the surface of the composite particles to form a coating gel, and obtain coated composite particles; S5, Secondary drying and shaping: The hot air drying function of the disc granulator is started to dry the coated composite granules at 55°C for 12 hours to dry the coating gel to form a solid coating; S6. Repeat steps S3-S5 2-3 times until the thickness of the coating on the surface of the coated composite particles reaches 1-2 mm, thereby obtaining the composite material.
[0023] Example 6 S1. Granulation: 67 parts of commercially available common fertilizer and 8 parts of sodium alginate are mixed and ground until the particle fineness is 60-80 meshes, so as to obtain a composite material, the composite material is put into a disc granulator, and 17 parts of a calcium chloride solution with a mass percentage concentration of 0.5% is sprayed, the humidity of the composite material is measured by a soil moisture sensor, and the humidity of the composite material powder is controlled at about 15-20%, too low or too high humidity will affect the granulation effect, the disc granulator is started for granulation, and when the granulation diameter reaches 3-4 mm, the disc granulator is stopped to obtain composite particles; S2. Drying: Start the hot air drying function of the disc granulator, set the drying temperature at 60 °C, and dry for 24 h; S3, forming a viscous adsorption gel: 6 portions of 0.5% calcium chloride solution by mass percentage are placed in the spraying device and sprayed on the dried composite particles. At the same time, the stirring function of the disc granulator is started to stir the particles so that the calcium chloride solution is evenly coated on the surface of the composite particles and reacts with the sodium alginate on the surface as follows: 2C 17 H 35 COO - +Ca 2+ ==(C 17 H 35 COO)2Ca A viscous adsorption gel is formed, and the amount of calcium chloride solution sprayed in this step does not exceed 7% of the mass of the composite particles; S4, Encapsulation: Start the stirring function of the disc granulator, add 1.4 parts of sodium polyacrylate powder with a fineness of 80-100 mesh to the material feeding device, the added amount is about 1.5% of the total mass of the composite particles obtained in step S3, slowly add the sodium polyacrylate powder to the disc granulator at a feeding speed of (10%×1.4 parts) / min, and stir at a speed of 15 r / min, so that the sodium polyacrylate powder is uniformly adsorbed on the surface of the composite particles to form a coating gel, and obtain coated composite particles; S5, Secondary drying and shaping: The hot air drying function of the disc granulator is started to dry the coated composite granules at 60° C. for 24 hours to dry the coating gel to form a solid coating; S6. Repeat steps S3-S5 2-3 times until the thickness of the coating on the surface of the coated composite particles reaches 1-2 mm, thereby obtaining the composite material.
[0024] Example 7 S1. Granulation: 68 parts of commercially available common fertilizer and 9 parts of sodium alginate are mixed and ground until the particle fineness is 60-80 meshes to obtain a composite material, the composite material is put into a disc granulator, and 16 parts of a calcium chloride solution with a mass percentage concentration of 0.4% is sprayed, the humidity of the composite material is measured by a soil moisture sensor, and the humidity of the composite material powder is controlled at about 15-20%, too low or too high will affect the granulation effect, the disc granulator is started for granulation, and when the granulation diameter reaches 3-4 mm, the disc granulator is stopped to obtain composite particles; S2. Drying: Start the hot air drying function of the disc granulator, set the drying temperature at 58 °C, and dry for 15 h; S3, forming a viscous adsorption gel: 4 portions of 0.4% calcium chloride solution by mass percentage are placed in the spraying device and sprayed on the dried composite particles. At the same time, the stirring function of the disc granulator is started to stir the particles so that the calcium chloride solution is evenly coated on the surface of the composite particles and reacts with the sodium alginate on the surface as follows: 2C 17 H 35 COO - +Ca 2+ ==(C 17 H 35 COO)2Ca A viscous adsorption gel is formed, and the amount of calcium chloride solution sprayed in this step does not exceed 5% of the mass of the composite particles; S4, Encapsulation: Start the stirring function of the disc granulator, add 1.4 parts of sodium polyacrylate powder with a fineness of 80-100 mesh to the material feeding device, the added amount is about 1.5% of the total mass of the composite particles obtained in step S3, slowly add the sodium polyacrylate powder to the disc granulator at a feeding speed of (6%×1.4 parts) / min, and stir at a speed of 15 r / min, so that the sodium polyacrylate powder is uniformly adsorbed on the surface of the composite particles to form a coating gel, and obtain coated composite particles; S5, Secondary drying and shaping: The hot air drying function of the disc granulator is started to dry the coated composite granules at 58°C for 15 hours to dry the coating gel to form a solid coating; S6. Repeat steps S3-S5 2-3 times until the thickness of the coating on the surface of the coated composite particles reaches 1-2 mm, thereby obtaining the composite material.
[0025] Example 8 S1. Granulation: 70 parts of commercially available common fertilizer and 10 parts of sodium alginate are mixed and ground until the particle fineness is 60-80 meshes to obtain a composite material, the composite material is put into a disc granulator, and 18 parts of a calcium chloride solution with a mass percentage concentration of 0.2% is sprayed, the humidity of the composite material is measured by a soil moisture sensor, and the humidity of the composite material powder is controlled at about 15-20%, too low or too high will affect the granulation effect, the disc granulator is started for granulation, and when the granulation diameter reaches 3-4 mm, the disc granulator is stopped to obtain composite particles; S2. Drying: Start the hot air drying function of the disc granulator, set the drying temperature at 59 °C, and dry for 20 h; S3, forming a viscous adsorption gel: 6 portions of 0.2% calcium chloride solution by mass percentage are placed in the spraying device and sprayed on the dried composite particles. At the same time, the stirring function of the disc granulator is started to stir the particles so that the calcium chloride solution is evenly coated on the surface of the composite particles and reacts with the sodium alginate on the surface as follows: 2C 17 H 35 COO - +Ca 2+ ==(C 17 H 35 COO)2Ca A viscous adsorption gel is formed, and the amount of calcium chloride solution sprayed in this step does not exceed 7% of the mass of the composite particles; S4, Encapsulation: Start the stirring function of the disc granulator, add 1.5 parts of sodium polyacrylate powder with a fineness of 80-100 mesh to the material feeding device, the added amount is about 1.5% of the total mass of the composite particles obtained in step S3, slowly add the sodium polyacrylate powder to the disc granulator at a feeding speed of (8%×1.5 parts) / min, and stir at a speed of 15 r / min, so that the sodium polyacrylate powder is uniformly adsorbed on the surface of the composite particles to form a coating gel, and obtain coated composite particles; S5, Secondary drying and shaping: The hot air drying function of the disc granulator is started to dry the coated composite granules at 59°C for 20 hours to dry the coating gel to form a solid coating; S6. Repeat steps S3-S5 2-3 times until the thickness of the coating on the surface of the coated composite particles reaches 1-2 mm, thereby obtaining the composite material.
[0026] The concentration of the calcium chloride solution has an important influence on the water absorption and swelling rate of the composite material. Five calcium chloride solutions with mass percentage concentrations of 0.1%, 0.3%, 0.5%, 1.0% and 3.0% were prepared according to Examples 1-5. The prepared composite material particles were placed in a beaker containing 100 ml of distilled water for 1 h to fully absorb water, and a gel was formed on the surface of the particles. The composite material particles were then taken out and the surface water was immediately removed with filter paper and weighed. Five groups of experiments were independently carried out at each concentration, and the water absorption and swelling rates were calculated respectively, and the average value was taken.
[0027] like Figure 1 As shown in the figure, as the concentration of calcium chloride solution increases from 0.1% to 0.5%, the water absorption and swelling rate of the composite material gradually increases, and when the concentration of calcium chloride solution exceeds 0.5%, the water absorption and swelling rate of the composite material no longer increases significantly. Therefore, the concentration of calcium chloride spray solution is determined to be 0.1%-0.5%, and the most suitable concentration is 0.5%.
[0028] Comparative Example 1: Ordinary fertilizer granules on the market do not contain sodium alginate, calcium chloride solution and sodium polyacrylate.
[0029] Comparative Example 2: Only sodium alginate and calcium chloride were added to the commercially available common fertilizers, and granulation was performed according to steps S1 and S2 of Example 6.
[0030] Take 10 particles of each of the composite particles of Comparative Example 1, Comparative Example 2, and Example 6 and place them in a culture dish. The diameter of the particles is measured. Then, 10 ml of water is sprayed on the culture dish. After 1 hour, the diameter and shape of the fertilizer after water absorption are measured to evaluate the expansion, water absorption, and stability of the composite material. After absorbing water for 1 h, the morphology of each material was observed. Figure 2-Figure 3 shown; specifically, Figure 2 A is the common composite particles of Comparative Example 1 which have been dissolved in water and have no obvious solid characteristics; Figure 2 In the figure B, the composite particles of ordinary fertilizer added with sodium alginate in comparative example 2 maintain a relatively regular spherical shape, but some particles have a phenomenon of transitional expansion leading to morphological collapse. The average diameter increases from 3.90 mm before water absorption to 6.52 mm after water absorption, and the volume expands 4.7 times. Figure 3 As shown; Figure 2The particles C in Example 6 maintained a relatively perfect spherical shape after absorbing water, and had good stability, indicating that the coating played a good role in binding and supporting the skeleton, and could maintain the bulk density and structure of the soil; the average diameter of the particles increased from 4.28 mm before absorbing water to 7.34 mm after absorbing water, and the volume expanded by 5.0 times. Figure 3 shown.
[0031] In other embodiments, chemical fertilizers can also be replaced with other water-soluble soil additives, such as microbial agents, to promote the release of soil nutrients, improve soil aggregate structure, and enhance plant resistance to stress; they can also be replaced with chitosan oligosaccharides to enhance soil water permeability and water retention capacity, which is beneficial to the root growth of plants. Chitosan oligosaccharides contain a variety of trace elements and amino acids and other nutrients that can increase soil fertility.
[0032] Based on the above technical scheme, the present application adopts the hygroscopic and swellable polymer material sodium alginate to improve the compaction problem. After sodium alginate is applied to the soil, it swells when it encounters water, and can maintain the soil bulk density and structure, solving the problem that traditional chemical fertilizers have almost no expansion when they encounter water after application, dissolve in a short time, and the ions in the fertilizer react with the soil particles. When the soil loses water, the aggregates are destroyed, causing compaction; applying chemical fertilizers to saline-alkali land overcomes the technical prejudice that traditional chemical fertilizers cannot be used in saline-alkali land and aggravate compaction; In order to solve the problem that the sodium alginate gel in the composite material is not strong enough and is easily broken and hydrolyzed in a high-salt and high-pH environment, calcium chloride solution is sprayed and a gel coating with stronger stability and toughness is formed by cross-linking the calcium chloride solution and sodium polyacrylate to improve the physical properties of the composite material such as water absorption, expansion and toughness, and improve the strength of the composite material. Composite materials with a specific coating thickness can be formulated through multiple coatings, which can effectively cope with the harsh environment of saline-alkali land. The composite material is stable after absorbing water and swelling, and its volume expands more than 5 times. When 10% of the composite material is added to the surface compacted soil, when the soil has sufficient moisture, the soil water holding capacity can be increased by 2-5%, and the soil bulk density can be reduced by 20-30%, which can significantly improve the problem of saline-alkali soil compaction. At the same time, as the coating slowly decomposes, the nutrients and calcium ions in the fertilizer are slowly released and exchanged with the sodium ions in the soil, which is beneficial to the desalination of saline-alkali soil.
[0033] Finally, it should be noted that: the various embodiments in this specification are described in a progressive manner, and each embodiment focuses on the differences from other embodiments. The same or similar parts between the various embodiments can be referenced to each other.
[0034] The above embodiments are only used to illustrate the technical solution of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, ordinary technicians in the field should understand that the specific implementation methods of the present invention can still be modified or some technical features can be replaced by equivalents without departing from the spirit of the technical solution of the present invention, which should be included in the scope of the technical solution for protection of the present invention.
Claims
1. A hygroscopic and expandable composite material, characterized in that: The raw material components include the following parts by weight: 65-70 parts of fertilizer, 7-10 parts of sodium alginate, 20-25 parts of calcium chloride solution, and 1-2 parts of sodium polyacrylate powder.
2. The hygroscopic and expandable composite material according to claim 1, characterized in that: The mass percentage concentration of the calcium chloride solution is 0.1%-0.5%.
3. The method for preparing the hygroscopic and expandable composite material according to any one of claims 1 to 2, characterized in that: The steps include: S1. Granulation: The fertilizer and sodium alginate are mixed and ground in proportion to obtain a composite material, the composite material is put into a granulator, and a calcium chloride solution is sprayed to control the humidity of the composite material within a certain range, and the granulator is started to granulate to obtain composite particles; S2. Drying: Drying the composite particles at 55-60°C for 12-24 hours; S3, forming a viscous adsorption gel: Spraying the calcium chloride solution onto the dried composite particles while stirring, so that the calcium chloride solution is evenly coated on the surface of the composite particles to form composite particles with a viscous adsorption gel on the surface; S4, Encapsulation: Adding sodium polyacrylate powder to the composite particles that form the viscous adsorption gel in step S3, and stirring the mixture, so that the sodium polyacrylate powder is uniformly adsorbed on the surface of the composite particles to form a coating gel, thereby obtaining coated composite particles; S5, Secondary drying and shaping: Drying the coated composite particles at 55-60° C. for 12-24 hours to dry the coating gel to form a solid coating; S6. Repeat steps S3-S5 until the thickness of the coating on the surface of the coated composite particles reaches the required value, thereby obtaining the composite material.
4. The method for preparing the hygroscopic and expandable composite material according to claim 3, characterized in that: In step S1, when the fineness of the composite material is 60-80 mesh, the grinding is stopped and the composite material is put into a granulator.
5. The method for preparing the hygroscopic and expandable composite material according to claim 4, characterized in that: In step S1, the humidity of the composite material is controlled at 15-20%.
6. The method for preparing the hygroscopic and expandable composite material according to claim 3, characterized in that: In step S3, the viscous adsorption gel is formed by the reaction of the calcium chloride solution and the sodium alginate on the surface of the composite particles, and the reaction formula is as follows: 2C 17 H 35 COO - +Ca 2+ ==(C 17 H 35 COO)2Ca。 7. The method for preparing the hygroscopic and expandable composite material according to claim 6, characterized in that: In step S3, the spraying amount of the calcium chloride solution does not exceed 5%-7% of the weight of the composite particles.
8. The method for preparing the hygroscopic and expandable composite material according to claim 3, characterized in that: In step S4, the fineness of the sodium polyacrylate powder is between 80-100 meshes.
9. The method for preparing the hygroscopic and expandable composite material according to claim 8, characterized in that: In step S4, the feeding speed of the sodium polyacrylate powder is 5%-10% / min of the total feeding mass of the sodium polyacrylate powder, and the stirring speed is 10-15 r / min.
10. Use of the hygroscopic expandable composite material prepared by the method according to any one of claims 3 to 9, characterized in that: Applied to the improvement of saline-alkali soil, the surface coating absorbs water and expands from a solid state to a semi-solid gel state, and the nutrients in the fertilizer are slowly released into the soil through the gel, and a microenvironment with a higher water content is formed in the soil. After the soil loses water, the coating also loses water and returns to a solid state, and no longer releases the nutrients in the fertilizer; after the soil is rehydrated again, the coating absorbs water and expands to a gel state again, and slowly releases the nutrients again, and the above process is repeated many times until all the nutrients in the fertilizer are released, and the coating gradually decomposes in the process of absorbing and losing water.
Citation Information
Patent Citations
Method for preparing granular compound fertilizer
CN101891543A
Compound water-retaining and slow-release fertilizer and preparation method thereof
CN106748001A
Calcium alginate-sodium polyacrylate modified composite membrane and preparation method thereof
CN112941926A
Sodium phosphate-based heat storage material
JP1999080722A